The Supposed Reversal Of Inheritance Of Ferrite Grain Size From That Of Austenite (45a24a31-640a-4c8a-9fcd-300edb714808) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
W. E., RUDER, Schenectady, N. Y. (written discussion *).-Professor Howe, with characteristic thoroughness, has demonstrated that Professor Jeffries' "Reversed Inheritance" explanation of the case in question is contrary to fact, as shown by many previous observers. Since the photographs were my own, I feel it my duty to say a few words in discussion. In the first place, it is to be noted that these photographs were of pressed powders, and although many of Professor Jeffries' original experiments were made from this kind of material, the nature of such a specimen must of necessity be different from that of the fused metal, although the same basic laws of grain growth may apply in both cases, certain factors, such as the rate of change, for example, are undoubtedly different in each case. That the 1000° C. grain is a natal grain is evident from its appearance contrasted with the more perfectly formed, though smaller, grains in the 1300° C. photograph. I am not sure that Professor Howe's explanation of the formation of this grain is necessarily the correct one, although it agrees with. Stead and Carpenter's results. I am inclined to think that this grain may have been formed on heating, because I have been able to produce grains of the shape and magnitude of Stead and Carpenter's grains by heating to 850° C. pure electrolytic iron, which has been subjected to a strain gradient. On reheating to 1300° C., the mobility being so much greater, the individual crystals had time for unhampered re-arrangement and growth after their second refinement on passing Ac3, so that we have in this case a true fused metal condition in which the individual crystals are arranged in true equiaxed grains of a size consistent with their high temperature anneal. In this case the grains are equiaxed, inheriting none of the columnar tendencies of the previous grain, because they were not affected by any strain gradient, except possibly some accidental local gradients. It seems to me that the introduction of pressed powders into the discussion of grain growth, where allotropic changes take place, unnecessarily complicates an already complicated problem.